Studying poetry - Spurr, Barry. (Macmillan Education Australia, 1997)
Reading poetry: Reading aloud, Describing a poem, Varieties of poetic style, Evaluation of poetry. Poetry through the centuries: the Renaissance, the early seventeenth century, the restoration and augustanism, romanticism...